THE EFFECT OF HEDONIC SHOPPING MOTIVATION ON IMPLUSIVE BUYING: THE MEDIATOR ROLES OF SHOPPING LIFESTYLE - Fadhilah, Maulia Kirana; Rejeki, Asri; Puspitaningrum, Noer Suci Endah (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
This study aims to determine the effect of hedonic shopping motivation on impulsive buying with a shopping lifestyle mediator on shopee consumers. This study used a quantitative approach using incidental sampling techniques and obtained a sample of 81 students from the Faculty of Economics and Business, Faculty of Teacher Training and Education, Faculty of Psychology, Univ Muhammadiyah Gresik, Class of 2017. The data collection method for hedonic shopping motivation, impulsive buying and shopping lifestyle variables used a questionnaire that compiled and modified by researchers in a Likert Scale. Test the validity of the scale using content validity. Scale reliability test using Alpha Cronbach technique. Data analysis using Multiple Regression based on Baron and Kenny (1986). The results of the analysis show that path c is accepted with a significant value of 0.000 (p<0.05), path a is not accepted with a value of 0.205 (p>0.05), path b is not accepted with a value of 0.596 (p>0.05), and path b is not accepted with a value of 0.596 (p>0.05), and path c' is not accepted with a value of 0.432 (p>0.05) getting a perfect mediation result. Subjects have a high category on the impulsive buying variable, a medium category on the hedonic shopping motivation variable and a low category on the shopping lifestyle variable.